Optimization of canal irrigation scheduling for Kharif crops in Mahanadi command area, Chhattisgarh - AGRAWAL, PURUSHOTTAM; VERMA, M. K.; SINHA, JITENDRA; NIGAM, G. K. (Journal of Soil and Water Conservation, 2020)
With growing population the demand of water for various purposes is ever increasing. On the other hand, the availability of water resources is limited in space and time, whereas demand of water for drinking, domestic, industrial as well as agriculture uses is increasing manifolds. A systematic and scientific planning for its optimal utilization is high imperative. Use of modern techniques in irrigation will go a long way in economizing consumption and saving of water which will bring greater areas under command and will ultimately result in more agricultural yield. Irrigation within the majority of rice growing area in Chhattisgarh has important social and economic benefits. There is 4.68Mha of net sown area available, out of which only 1.85Mha (33%) area is under irrigation and 2.83Mha net sown area is still without irrigation facilities. Present irrigation potential utilization is only1.26 Mha (68.70%) out of the available 1.85Mha of irrigation potential created so for. The reasons behind this deficit is because of heavy canal losses, improper traditional and unmanaged irrigation practices like inadequate and ill-timed, long duration and unsystematic canal water supply, without looking to actual crop water requirement, thereby wasting water to nearby streams. Irrigation scheduling is an important tool for optimizing the use of water resources where irrigated agriculture has a long tradition. Therefore, optimization of canal irrigation scheduling for kharif crops, through the application of the CROPWAT8 computer model by considering the average rainfall, soil and weather parameters over the study area has been presented in this paper. The design discharge volume of water in the study area of distributary - 4 (Dy-4) of lower bank canal (LBC) of Mahanadi Main Canal (MMC) in Pallari block of District Balodabazar, is about 20.8 Mm3 (during average canal supply), but out of which average actual supply is only 11.38 Mm3, which is only 54% of average designed discharge quantity. During the Kharif season crop water requirement (CWR) scheme supply requires only 3.66 Mm3 after optimization, which is only 32% quantity against actual average canal supply, thereby saving of 68% of water could be accomplished. The scheme supply requires only 55 days against 95 days of canal regulation in traditional practice.